Information systems security 6th International Conference, ICISS 2010, Gandhinagar, India, December 17-19, 2010. Proceedings - Jha, Somesh; Mathuria, Anish (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Information Systems Security, ICISS 2010, held in Gandhinagar, India, in December 2010. The 14 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 51 initial submissions. The papers are organized in topical sections on integrity and verifiability, web and data security, access control and auditing, as well as system security.